2015
DOI: 10.1159/000430221
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Propolis Enhances Cutaneous Wound Healing by Promoting TGF-Beta/Smad-Mediated Collagen Production in a Streptozotocin-Induced Type I Diabetic Mouse Model

Abstract: Background/Aims: Impaired wound healing is considered to be one of the most serious complications associated with diabetes as it significantly increases the susceptibility of patients to infection. Propolis is a natural bee product used extensively in foods and beverages that has significant benefits to human health. In particular, propolis has antioxidant, anti-inflammatory and analgesic effects that could be useful for improving wound healing. In this study, we investigated the effects of topical application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 56 publications
6
105
0
2
Order By: Relevance
“…In this context, we previously demonstrated the beneficial effects of TQ in the induction of growth arrest of multiple myeloma cancer cells and its protective anti-diabetic effects [36][37][38][39]. Moreover, we provided clear evidence for the effects of other natural antioxidants (camel whey protein and bee propolis) as immune-modulators in accelerating the healing process of diabetic wounds in experimental animal models [40][41][42][43][44][45][46]. Most interesting, we demonstrated that natural antioxidants isolated from snake and ant venoms enhanced normal lymphocyte functions and exerted antitumor effects in different human and animal cancer cells [47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 78%
“…In this context, we previously demonstrated the beneficial effects of TQ in the induction of growth arrest of multiple myeloma cancer cells and its protective anti-diabetic effects [36][37][38][39]. Moreover, we provided clear evidence for the effects of other natural antioxidants (camel whey protein and bee propolis) as immune-modulators in accelerating the healing process of diabetic wounds in experimental animal models [40][41][42][43][44][45][46]. Most interesting, we demonstrated that natural antioxidants isolated from snake and ant venoms enhanced normal lymphocyte functions and exerted antitumor effects in different human and animal cancer cells [47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 78%
“…The transforming growth factor (TGF)-β/Smad signaling pathway plays an important role in a variety of processes including cell growth, proliferation, differentiation and apoptosis, and TGF-β is involved in many fibrotic diseases including keloids through its role in promoting extracellular matrix (ECM) production and tissue fibrosis [17,18]. TGF-β is a member of a family of secreted cytokines that binds to and induces the dimerization of TGF-β type II receptors and the subsequent phosphorylation of TGF-β type I receptors, which phosphorylate Smad2/3 leading to the translocation of Smad4 to the nucleus and the activation of the expression of target genes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, compared with untreated diabetic mice, the treatment of diabetic mice with propolis significantly enhanced the production of collagen via the TGF-β/Smad2, 3 signalling axis in wounded tissues (Hozzein et al, 2015).…”
Section: Propolismentioning
confidence: 96%
“…Moreover, the wound tissues of diabetic mice showed a marked reduction in the phosphorylation of Smad 2 and Smad 3 as well as a marked reduction in collagen production (Hozzein et al, 2015). Smads are intracellular proteins that transduce extracellular signals from transforming growth factor beta ligands to the nucleus.…”
Section: Diabetic Ulcersmentioning
confidence: 99%